The Economic Impact of Halal Tourism in Muslim and Non-Muslim Countries: A Comparative Study of Indonesia, Hong Kong, and Africa - Adinugraha, Hendri Hermawan; Ismanto, Kuat; Shulthoni, Muhammad (Eco-Tourism and Sustainable Development, 2026)
This research examines and compares the economic impact of halal tourism in Muslim and non-Muslim contexts, analyzing Indonesia, Hong Kong, and selected African countries. It aims to identify how demographic, policy, and socio-cultural factors shape halal tourism’s contribution to economic development. The research employs a qualitative approach, utilizing a systematic literature review. Academic journals, international reports, and policy documents published between 2010 and 2023 were analyzed through content and comparative analyses to assess halal tourism’s contribution to gross domestic product (GDP) growth, employment, and Micro, Small, and Medium Enterprises (MSME) development across the three regions. The findings reveal that halal tourism generates significant economic benefits in Indonesia, thanks to strong regulatory support, cultural alignment, and the empowerment of MSMEs. In Hong Kong, halal tourism contributes moderately by attracting high-spending Muslim tourists through adaptive market strategies despite a small domestic Muslim population. In Africa, the economic impact remains limited but shows strong potential, particularly in countries with Islamic heritage, which is constrained mainly by weak infrastructure and inadequate policy support. The study highlights the importance of context-specific strategies in maximizing the economic impact of halal tourism and supports the multiplier effect theory in tourism economics. This research provides a cross-regional comparative framework that integrates economic, cultural, and policy perspectives in halal tourism studies.